Addressing the UN SDGs in sustainability reports : an analysis of Latin American oil and gas companies - Fabíola M. M. G. Borges and Izabela Simon Rampasso and Osvaldo Luiz Goncalves Quelhas and Walter Leal Filho and Rosley Anholon (Environmental challenges, 2022)
This article aims to establish an overview of the sustainable practices developed by the major oil and gas enterprises in Latin America and analyse how these practices are related to the Sustainable Development Goals (SDGs) 7, 9, 11 and 12. The methodological strategy used was the content analysis of the sustainability reports published by companies in the sector. Considering the ten oil and gas companies with the highest revenue in Latin America, 7 of them published sustainability reports in 2020 (base 2019), and these reports were analysed via content analysis technique. The findings showed that 244 sustainable practices were reported in sustainability reports by these seven companies. These practices were summarised by twenty different keywords (the practice can be represented by more than one keyword) and related with the targets of SDGs 7, 9, 11 and 12. It was found that few practices were related with the following targets: (a) greater access of small-sized companies, especially from developing countries, to financial services (target 9.3), (b) encouragement of companies to use sustainable practices and add sustainability information in their reporting cycle (target 12.6) and (c) the rationalisation of inefficient fossil-fuel subsidies (target 12.c). However, one company stands out amongst its competitors, having practices that, on average, were related with a higher number of targets of SDGs 7, 9, 11 and 12. This research has an exploratory character. The information reported here is of great value in guiding CSR actions of companies in the oil and gas sector and future research in the area to discuss how such companies can contribute to targets 9.3, 12.6, and 12.c.
Keywords: Oil and gas industry; SDGs; Sustainability; Sustainability reports